PENERAPAN BLUE ECONOMY DALAM PENGEMBANGAN PENDAPATAN PELAKU USAHA PERIKANAN DI KAMPUNG HAMADI KOTA JAYAPURA: - Tuhumena, Lolita; Rumahorbo, Basa T.; Wambrauw, Daniel Z.K.; Battu, Yudistira S.; Karisoh, Gabriela O.; Umbekna , Sara; Paranoan, Nicea Roona; Hehanussa, Kedswin G. (Jurnal Abdi Insani, 2024)
Processed products in Hamadi Village only rely on the type of processed fish smoked produced by Fishery Business Actors, namely POKLAHSAR Mama Papua. Efforts to maximize the acceptance of processed fishery products and meet market demands can be done by improving the appearance of the product, so that old buyers want to buy more products with a new appearance both in terms of shape, size, style, packaging, and taste. This can be done by making other breakthroughs such as value-added processed fishery products. This program used PRA (Participatory Rural Appraisal) method is one of the methods that can be applied. After getting pretest and posttest scores, must conduct an analysis to get the score obtained. The analysis used is uji normalitas gain. This test is used to determine the effectiveness of the treatment given. Implementation of community partnership service activities to POKLAHSAR Mama Papua in Hamadi village with providing training in the manufacture of a variety of processed fishery products. A variety of processed fishery products that have been made such as; Meatballs, Shredded Fish, Suir-Suir and Sambal whose meat is from Yellow Fin Tuna (Thunnus albacares). Furthermore, make packaging for a variety of processed fisheries and don't forget to teach partners about the importance of making simple bookkeeping by making pre-test and post test about bookkeeping knowledge. Then socialization about making NIB (Nomor Izin Berusaha) online and training in making social media in marketing a variety of processed fishery products, This is done to increase income POKLAHSAR Mama Papua in Hamadi village.